Genetic Diversity Among Ten Maize Genotypes Using Simple Sequence Repeat DNA Markers - Sebar D. Abdulazeez; Sakar A. Kakarash; Namam B. Ismael (Polytechnic Journal)
Genetic diversity among ten maize genotypes (seven inbred lines and three testers) was investigated using ten simple sequence repeats (SSRs). Primers (bnlg128, bnlg1839, Umc1117, bnlg1144, and bnlg1152) generated the highest number of bands (4 bands) for inbred lines while the primer bnlg128 showing the highest number of bands (3 bands) for testers. The primer bnlg128 shows the highest effective number of alleles (ne ) for inbred lines and testers. Among the studied primer bnlg1839 in inbred lines and primer bnlg128 in testers showed the maximum polymorphism information content (PIC) and the greatest diversity. Using UPGMA cluster analysis, the seven inbred lines were grouped under three clusters, while grouped the testers under two clusters. Most of the inbred lines which were derived from the same source population were grouped in the same cluster based on the SSRs DNA markers, indicating high genetic differentiation among their source populations. Results showed that the SSRs were informative in detecting genetic differences among the maize inbred lines and testers, as exhibited by the high average of Shannon’s information index (I), Nei’s expected heterozygosity (Nei’s), and PIC. The results suggest that the studied genotypes are diverse and may be utilized for further breeding programs.